School Teachers’ Experiences in Adopting Inclusive Practices in Integrated Classrooms of Nepal - Neupane, Nam Raj; Giri, Ram Chandra (Tribhuvan University Journal, 2021)
This study aimed to investigate the experiences of teachers of integrated schools in adopting inclusive practices in the classrooms. It was carried out by selecting three integrated schools of two districts, Kathmandu and Kavre, by purposive sampling method. Three teachers from each school were selected by purposive sampling method. The interview guidelines were prepared and got reviewed from a special needs education expert to maintain its reliability, and then administered to the participants. The study found that teachers have been experiencing low self-awareness on teaching students with disabilities. The study also showed a serious lacking in knowledge and skills in teachers and their deviated perceptions towards inclusive practice. Moreover, the study revealed that the school administration can play vital role in developing inclusive culture inside the school and also responsible to provide training to the teachers. Therefore, teachers being the key player in school system, need professional development and exposure to enhance knowledge and skills to handle students with special needs in integrated classrooms.